Quality of life and its association with cardiovascular risk factors in a community health care program population - Martinelli, Luiz Mário Baptista [UNESP]; Mizutani, Bruno Moreira [UNESP]; Mutti, Anibal [UNESP]; D'elia, Maria Paula Barbieri [UNESP]; Coltro, Rodrigo Soler [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2008)
OBJECTIVE: To evaluate quality of life in a population that attended a specific community event on health care education, and to investigate the association of their quality of life with the presence of cardiovascular risk factors INTRODUCTION: Interest in health-related quality of life is growing worldwide as a consequence of increasing rates of chronic disease. However, little is known about the association between quality of life and cardiovascular risk factors. METHODS: This study included 332 individuals. Demographics, blood pressure, body mass index, and casual glycemia were evaluated. The brief version of the World Health Organization Quality of Life questionnaire on quality of life was given to them. The medians of the scores obtained for the physical, psychological, emotional, and environmental domains were used as cutoffs to define higher and lower scores. A multinomial logistic regression model was used to define the parameters associated with lower scores. RESULTS: Diabetes mellitus, dyslipidemia, and obesity were associated with lower scores in the physical domain. Dyslipidemia was also associeted with lower scores in the psychological domain. Male gender and regular physical activity had protective effects on quality of life. Aging was inversely associated with decreased quality of life in the environmental domain. CONCLUSION: The presence of cardiovascular risk factors is related to a decreased quality of life. Conversely, male gender and regular physical activity had protective effects on quality of life. These findings suggest that exercising should be further promoted by health-related public programs, with a special focus on women.
Keywords: Blood pressure; Old age; Diabetes mellitus; Obesity; Female gender